Diversity Climate Perceptions [FRS] - Silva, S.A. (Research Seminar in the PhD program in Human Resources, University of Seville [FRS], 2018)
In this seminar it will be covered the topic of Diversity Climate considering the following sections: -Diversity Climate Introduction -Examples of my research on the topic -Challenges, future avenues, for diversity climate studies